Factores asociados al rendimiento académico en adultos - Vergel-Ortega, Mawency; Martínez-Lozano, José Joaquín; Zafra-Tristancho, Sandra Lilianal (Revista Científica, 2016)
The article has the objective identify the associated factors to academic performance of adult students in mathematics and statistics modules. Was realized a study quantitative correlational in a sample of 80 students with age over 30 years old. A group of institutional aspects, social-demographics, psychosocials and pedagogic factors were used as independent variable. Results indicate that style of learning associated with type of intelligence, deficit conscience associated to abstraction capability and family motivation predicts the higher levels of performance, constituting explicative variables. Conclusion: type and style of learning, type of intelligence, motivation, conscience of deficit are associated factors to performance in adults.